Nurses’ Reflections on Challenges and Barriers of Communication in The Intensive Care Unit: A Phenomenology Study - Etika Emaliyawati; Restuning Widiasih; Titin Sutini; Ermiati Ermiati; Urip Rahayu (Faculty of Nursing Universitas Padjadjaran, 2020)
Communication among nurses, patients, and families takes an important role in the intensive care unit in which the patients are in critical condition and unable to involve in two-way communication. Research related to effective nurse-patient communication has been done extensively, but the information regarding communication in intensive care unit is still limited. This research aimed to explore nurses’ experiences in the intensive care units in effective communication to patients/patient’s families. This was a qualitative study project with phenomenology approach. The data were collected using the in-depth interview technique approximately 60 minutes involving ten nurses who were selected using the purposive sampling at Al Islam Hospital Bandung. Data were analysed using the Colaizzi method and the results were presented in themes. Based on the nurses’ experiences, four themes were emerged in this study including (1) Nurses’ dilemma of their professionalism and personal issues/matters, (2) Contextual factor affects selection of nurses’ communication technique, (3) Barriers in effective communication; difficulties in accompanying families to accept critical patient conditions, care and treatment procedures in the ICU which were complicated, and misunderstanding between nurse-patient and family (4) Compassion and patience are required in nurse-patient communication in ICU. The complex patient/family conditions in the ICU require nurses to choose the appropriate communication technique accompanied by a sense of compassion and patience. Nurses need to improve their ability to communicate effectively in order to lower the barriers in communicating between nurses-patients/families. Recommendations, training and assistance of effective communication become important for nurses in improving services in the Intensive Care Unit.